Soil multifunctionality is affected by the soil environment and by microbial community composition and diversity. (September 2019) - Zheng, Qing; Hu, Yuntao; Zhang, Shasha; Noll, Lisa; Böckle, Theresa; Dietrich, Marlies; Herbold, Craig W.; Eichorst, Stephanie A.; Woebken, Dagmar; Richter, Andreas; Wanek, Wolfgang
Abstract: Microorganisms are critical in mediating carbon (C) and nitrogen (N) cycling processes in soils. Yet, it has long been debated whether the processes underlying biogeochemical cycles are affected by the composition and diversity of the soil microbial community or not. The composition and diversity of soil microbial communities can be influenced by various environmental factors, which in turn are known to impact biogeochemical processes. The objectives of this study were to test effects of multiple edaphic drivers individually and represented as the multivariate soil environment interacting with microbial community composition and diversity, and concomitantly on multiple soil functions (i.e. soil enzyme activities, soil C and N processes). We employed high-throughput sequencing (Illumina MiSeq) to analyze bacterial/archaeal and fungal community composition by targeting the 16S rRNA gene and the ITS1 region of soils collected from three land uses (cropland, grassland and forest) deriving from two bedrock forms (silicate and limestone). Based on this data set we explored single and combined effects of edaphic variables on soil microbial community structure and diversity, as well as on soil enzyme activities and several soil C and N processes. We found that both bacterial/archaeal and fungal communities were shaped by the same edaphic factors, with most single edaphic variables and the combined soil environment representation exerting stronger effects on bacterial/archaeal communities than on fungal communities, as demonstrated by (partial) Mantel tests. We also found similar edaphic controls on the bacterial/archaeal/fungal richness and diversity. Soil C processes were only directly affected by the soil environment but not affected by microbial community composition. In contrast, soil N processes were significantly related to bacterial/archaeal community composition and bacterial/archaeal/fungal richness/diversity but not directly affected by the soil environment. This indicates direct control of the soil environment on soil C processes and indirect control of the soil environment on soil N processes by structuring the microbial communities. The study further highlights the importance of edaphic drivers and microbial communities (i.e. composition and diversity) on important soil C and N processes. Highlights: Same edaphic factors shaped both bacterial/archaeal and fungal communities. Soil environment directly affected soil C processes. Bacterial/archaeal communities affected soil N processes. Both bacterial/archaeal and fungal diversity were linked to soil N processes.